2016
DOI: 10.5935/1678-9741.20160032
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of common iliac arteries after endovascular infrarenal abdominal aortic repair with bell-bottom extension

Abstract: ObjectiveEndovascular techniques to treat abdominal aortic aneurysms results in lower morbidity and mortality rates. However, dilation of the common iliac arteries prevents adequate distal sealing, which compromises the procedure success. The aim of this study is report the long-term outcomes of patients with abdominal aortic aneurysms associated with aneurysm of the common iliac artery following endovascular repair using a bifurcated bell-bottom stent graft.MethodsThis is a retrospective study that evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In the first two years after EVAR, younger patients showed significantly more dilatation of the vessel within the first two years compared to older patients. Similar results were shown in a study by Telles et al [ 15 ]. Our study suggests that next to oversizing, age also plays a possible role in changes in the iliac anatomy.…”
Section: Discussionsupporting
confidence: 93%
“…In the first two years after EVAR, younger patients showed significantly more dilatation of the vessel within the first two years compared to older patients. Similar results were shown in a study by Telles et al [ 15 ]. Our study suggests that next to oversizing, age also plays a possible role in changes in the iliac anatomy.…”
Section: Discussionsupporting
confidence: 93%
“…Progressive dilatation of ectatic iliac arteries has been described by several authors and is also associated with the displacement of the iliac grafts. 14,15 Griffin et al. reported that the rate of CIA diameter increase is significantly higher in patients with BBT than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Telles et al. 15 described a series of patients with CIAs larger than 15 mm with the incidence of type IB endoleak of 17.6% and reoperation rate of 15.7%. Studies with longer follow-up periods demonstrate higher type IB endoleak rates in consonance with our finding of higher type IB endoleak rate in late follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The other studies which include the bell-bottom technique report a higher rate of type Ib endoleak and reintervention, 18,19 suggesting that a longer follow-up period (usually after 3 years) is needed to observe the degeneration of an aneurysm at the distal stent graft location. Agu et al 20 reported a 2.4% incidence of developing iliac artery aneurysm in a 5 to 9 years of follow-up in 297 patients treated with EVAR with suitable distal landing zones, and they suggest Fig.…”
Section: Discussionmentioning
confidence: 99%